Obtaining and Characterizing Alginate/k-Carrageenan Hydrogel Cross-Linked with Adipic Dihydrazide. (31st December 2013) - Paşcalău, Violeta; Popescu, Violeta; Popescu, George L.; Dudescu, Mircea C.; Borodi, Gheorghe; Dinescu, Adrian M.; Moldovan, Marioara
Abstract : The aim of this paper is obtaining and characterizing hydrogels based on different ratios of oxidized alginate (oA) and k-carrageenan (C), chemically cross-linked with adipic dihydrazide (adh). The alginate (A) was first oxidized with sodium metaperiodate in order to transform it into the dialdehyde derivative, a more reactive compound than alginate. A known procedure for oxidation of alginate with sodium metaperiodate in ethanol-water in order to improve alginate reactivity by transforming the hydroxyl end-groups into dialdehyde was used, preceded by a partially cleavage of the alginate chains. In the second stage, the mixture of dialdehydic derivative of oxidized alginate, k-carrageenan and glycerol subjected to reaction with adipic dihydrazide leads to a Semi-Interpenetrated Network covalently cross-linked alginate/k-carrageenan hydrogel (oACadh ), based on the dihydrazone compound which is responsible for the chemical cross-linking. Pure alginate, k-carrageenan, oxidized alginate, adipic dihydrazide and the cross-linked hydrogel were characterized by: FTIR, XRD, and SEM.